Hubungan sanitasi dasar dengan kejadian stunting - Mariana, Rani; Nuryani, Dina Dwi; Angelina, Christin (JOURNAL OF Community Health Issues, 2024)
Background: Data on the prevalence of stunting according to the World Health Organization (WHO), Indonesia is the third country with the highest prevalence in the Southeast Asia/South-East Asia Regional (SEAR) region. Currently, more than a third of children under five (37.2%) in Indonesia suffer from stunting. Lampung is the fifth province with the highest stunting (42.63%), in Metro City as many as 751 toddlers (9.57%) experience stunting and Central Metro District has the largest number of stunting cases as many as 306 toddlers. Purpose: To determine the relationship between basic sanitation and the incidence of stunting in the Yosomulyo Health Center Work Area, Metro District, Metro City Center in 2021. Method: This type of research is quantitative with a cross sectional design. The population of all children's homes in the Yosomulyo Health Center's Working Area is 1,692 toddlers. Samples were taken as many as 119 people. Data collection by observation and checklist sheets. The statistical test used is the chi square test. Results: The study showed that there was a relationship between healthy latrines (p value = 0.006; OR = 3.895), clean water facilities (p value = 0.015; OR = 3.574), waste disposal (p value = 0.004; OR = 4.884) and SPAL (p value = 0.041; OR = 2.854). Conclusion: All variables are related to the incidence of stunting because the p-value < 0.05. Furthermore, the puskesmas should always pay attention to and promote the importance of environmental health both inside and outside the home. Keywords: Stunting; Basic sanitation; Toddler Pendahuluan: Data prevalensi stunting menurut World Health Organization (WHO), Indonesia termasuk negara ketiga dengan prevalensi tertinggi di regional Asia Tenggara/South-East Asia Regional (SEAR). Saat ini lebih dari sepertiga jumlah balita (37,2%) di Indonesia menderita stunting. Lampung menjadi provinsi kelima tertinggi stunting sebesar (42,63%), di Kota Metro sebanyak 751 balita (9,57%) mengalami stunting dan Kecamatan Metro Pusat memiliki angka kasus stunting terbesar sebanyak 306 balita. Tujuan: Untuk mengetahui hubungan sanitasi dasar dengan kejadian stunting di Wilayah Kerja Puskesmas Yosomulyo Kecamatan Metro Pusat Kota Metro Tahun 2021. Metode: Jenis penelitian kuantitatif dengan desain cross sectional. Populasi seluruh rumah balita di Wilayah Kerja Puskesmas Yosomulyo sebanyak 1.692 balita. Sampel diambil sebanyak 119 orang. Pengumpulan data dengan observasi dan lembar ceklist. Uji statistik yang digunakan adalah uji uji chi square. Hasil: Penelitian menunjukkan bahwa ada hubungan jamban sehat (p value = 0,006; OR = 3,895), sarana air bersih (p value = 0,015; OR = 3,574), pembuangan sampah (p value = 0,004; OR = 4,884) dan SPAL (p value = 0,041; OR = 2,854). Simpulan: Semua variabel berhubungan dengan kejadian stunting karena nilai p-value < 0.05. Selanjutnya pihak puskesmas untuk selalu memperhatikan dan mempromosikan pentingnya kesehatan lingkungan di dalam rumah maupun di luar rumah. Kata kunci: Stunting; Sanitasi dasar; Balita